Anomaly Response Spectrum of Various Cities in Indonesia Based on SNI 1726:2019 - Anis Rosyidah; Ulil Albab; Rinawati; I Ketut Sucita; Latha M. S (Recent in Engineering Science and Technology, 2023)
Response spectra that happened anomaly is seen after SNI 1726:2012 dan SNI 1726:2019 published, this condition has happened because the value of response spectrum design is SE < SD < SC, SD < SE < SC, or SD < SC < SE, if this in normal condition, the value of response spectrum is SC < SD < SE. With applied methods and procedures found by Kircher & Associates (2015) they adjust the formula SMS & SM1 wished response spectrum becomes normal. In this research, comparing spectrum response, with spectrum response with treatment, and comparing the value SDS dan SD1. From this research, it was found that there was a decrease in seismic loading on hard soil (SC) and an increase in medium soil (SD) and soft soil (SE).